H2O CONCENTRATIONS IN PRIMARY MELTS FROM SUPRA-SUBDUCTION ZONES AND MID-OCEAN RIDGES: IMPLICATIONS FOR H2O STORAGE AND RECYCLING IN THE MANTLE - Sobolev A.V.; Chaussidon M. (My University, 1996)
A total of 145 inclusions, trapped and isolated in Mg-rich olivine phenocrysts (Fo0.87–0.94) from basalts and ultramafic lavas, and representing the most primitive mantle melts known, have been analysed by ion microprobe for their H2O contents. This approach allows us to conduct a general survey of the distribution of water in primary melts derived from the mantle beneath mid-ocean ridges and above subduction zones. The primitive melts included in MORB olivines have low H2O contents (mean at 0.12 wt% for N-MORB (14 samples), 0.17 wt% for T-MORB (9 samples) and 0.51 wt% for E-MORB (14 samples)). A strong decoupling between H2O and K2O has been found in some MORB primary melts which might well be explained by the presence of a H2O-bearing CO2-rich fluid. In contrast with mid-ocean ridges, primitive melts of subduction zones basalts are very rich in H2O (between 1.0 and 2.9 wt% (mean at 1.7 wt%, 84 samples) for boninites and between 1.2 and 2.5 wt% (mean at 1.6 wt%, 24 samples) for island arc tholeiites). In addition, most of these melts have high H2O/K2O ratios which are consistent with a transfer of H2O as a fluid phase from the subducted slab to the mantle wedge. For boninites and island arc primary melts, the present H2O contents are ≈ 2.5 × higher than commonly assumed, which suggests that the amount of H2O released to the surface in arc magmatism has been previously underestimated.